Integration of Tringo Concept Ki Hadjar Dewantara in Development of Islamic Education Learning Evaluation - Markus, Markus; Abu Bakar, M. Yunus; Kholis, Nur (Letiges, 2023)
This study focuses on integrating the Tringo Ki Hadjar Dewantara concept into the evaluation of Islamic education learning, aiming to enhance the educational function of assessing students' abilities in the learning process. The Tringo Ki Hadjar Dewantara concept is identified as a suitable framework for integration into the independent curriculum's learning evaluation. The research employs a literature study approach to elucidate these two aspects. The study uses content analysis and interpretation for data analysis, drawing from primary and secondary data sources. Using a deductive approach, the author collects and synthesizes relevant literature to contextualize the research discussion. The research addresses a crucial need due to the adaptable nature of the independent curriculum, requiring concept comparisons and adjustments, particularly in the realm of Islamic education. The study's novelty lies in integrating the Tringo Ki Hadjar Dewantara concept into the development of Islamic education learning evaluation. This uniqueness stems from the need for prior research on this concept's connection with learning evaluation. While existing studies have explored the Tringo concept's application in various educational contexts, they have yet to examine its integration into the assessment of Islamic education. Therefore, this study addresses an unexplored area within educational practice. By integrating the Tringo concept, educational practitioners can conduct comprehensive checks encompassing cognitive, affective, and psychomotor domains. These innovative evaluation approaches can be effectively implemented in Islamic education, leading to more impactful and engaging learning experiences.